2018
DOI: 10.1038/s41586-018-0433-3
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-kinase 1 is a cytosolic innate immune receptor for bacterial ADP-heptose

Abstract: Immune recognition of pathogen-associated molecular patterns (PAMPs) by pattern recognition receptors often activates proinflammatory NF-κB signalling. Recent studies indicate that the bacterial metabolite D-glycero-β-D-manno-heptose 1,7-bisphosphate (HBP) can activate NF-κB signalling in host cytosol, but it is unclear whether HBP is a genuine PAMP and the cognate pattern recognition receptor has not been identified. Here we combined a transposon screen in Yersinia pseudotuberculosis with biochemical analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
258
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 183 publications
(301 citation statements)
references
References 39 publications
13
258
0
Order By: Relevance
“…Recognition is specific, as evidenced by the fact that the α-configurated forms elicited no response. By directly demonstrating that ADP heptose is present in gram-negative bacteria at sufficient concentrations, these results complement the recent demonstration by Zhou et al (12) that ADP heptose is the ligand for ALPK1.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Recognition is specific, as evidenced by the fact that the α-configurated forms elicited no response. By directly demonstrating that ADP heptose is present in gram-negative bacteria at sufficient concentrations, these results complement the recent demonstration by Zhou et al (12) that ADP heptose is the ligand for ALPK1.…”
Section: Discussionsupporting
confidence: 86%
“…After screening fractionated H. pylori lysates for their capacity to stimulate NF-κB, we identified ADP heptose by MS as a novel, potent NF-κB–activating PAMP acting via the ALPK1-TIFA signaling axis [see also Pfannkuch et al (11)]. In parallel to our studies, Zhou et al (12) recently demonstrated that ADP heptose is indeed the ligand for ALPK1. Because ADP heptose is present in most LPS-containing bacteria, this molecule likely is of relevance for numerous infections with gram-negative bacteria.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…4 Initially, it was reported that TIFA is responsible for H pylori T4SS-dependent proinflammatory responses via its recognition of the LPS intermediate metabolite, heptose-1,7-bisphosphate (HBP). Elegant biochemical studies showed that the N-terminal domain of ALPK1 directly binds ADP-heptose, which leads to the phosphorylation and activation of the adaptor molecule, tumor necrosis factor (TNF), a receptor-associated factor-interacting protein with a forkhead-associated domain (TIFA).…”
mentioning
confidence: 99%
“…In conclusion, our data rule out a major contribution of βHBP in S. flexneri infection and identify ADP‐heptose as a new potent bacterial PAMP that can be detected down to a concentration of 10 −10 M. The delay in inflammatory signaling observed in response to βHBP suggested that this bacterial metabolite is not directly recognized by host defense mechanisms. At the time of finalizing this manuscript, Zhou et al confirmed this hypothesis by showing that βHBP must be converted into ADP‐heptose 7‐phosphate by host adenylyltransferase enzymes of the NMNAT family to induce inflammatory signaling. Although βHBP is a bacteria‐derived factor triggering an immune response, its classification as a genuine PAMP is challenged by the fact that it is not directly sensed via the interaction with a cognate pathogen recognition receptor.…”
Section: Resultsmentioning
confidence: 92%